Prawna regulacja rolnictwa ekologicznego – próba oceny - LEŚKIEWICZ, KATARZYNA (Wydawnictwo Naukowe UAM, 2010)
The paper presents an attempt to evaluate the legal regulation of organic agriculture taking into consideration three reference points, i.e. relationships between properties of organic agricultural products ascribed to them by the legislator and properties of these products proposed by science, stipulations of legal solutions (institutions), which are to provide an assurance of organic products having properties indicated by the legislator, and the evaluation of the impact of such indicated legal solutions on the assurance that agricultural products labelled as organic have properties indicated by the legislator. The biggest objections are voiced in relation to a certain discrepancy between potential deviations from the requirements concerning organic production declared admissible by the legislator and scientific proposals referring to the principles of this production. Numerous possible deviations result in the fact that such understood quality of organic products differs from the model indicated by science. Legal solutions concerning the consistency of organic products with the requirements specified by the legislator are to provide this consistency at a high degree, but not in an absolute manner, since the legal regulation itself is not perfect in this respect and at the same time it is not always appropriately applied.

Lo scritto valuta la disciplina giuridica dell’agricoltura biologica formulando l’indagine attraverso il raffronto tra le caratteristiche biologiche dei prodotti agricoli secondo il legislatore e le caratteristiche di tali prodotti così come auspicate dalla scienza; formulando le soluzioni che dovrebbero garantire ai prodotti biologici le qualità indicate dal legislatore; nonché valutando la capacità delle proposte legislative di assicurare ai prodotti indicati come biologici le qualità organolettiche che dovrebbero possedere per essere definiti appunto biologici. Viene, in particolare, in evidenza la divergenza esistente tra le possibili deroghe ai requisiti dei prodotti biologici ammessi dal legislatore e quelli postulati degli scienziati, soprattutto, in relazione alle regole di produzione. Tali deroghe infatti fanno sì che la qualità, così intesa, dei prodotti biologici si discosti dal modello indicato dalla scienza. Del resto interventi legislativi volti a conformare i prodotti biologici ai requisiti determinati dalla scienza se da un lato potrebbero assicurare tale conformità, dall’altro, la possibilità di perseguire l’obiettivo non è assoluta, poiché in questo ambito il ricorso alla disciplina giuridica non è sempre opportuna, inoltre non è sempre correttamente applicata.